Improve Healthcare Accessibility via a Mobile App for Health Facility Search Utilizing Location-Based Services - Zulkarnain, Adnan; Gibran, Devid (IC-ITECHS, 2024)
Access to health facilities is an important aspect of individual well-being but many communities, especially in remote areas, face difficulties in finding and accessing health services. Location-Based Services (LBS) technology in mobile applications offers a solution to this problem. This research aims to develop and test an LBS-based mobile application to improve the accessibility of health facilities. Using applied design, applications are developed for Android platforms. The sample consisted of 100 respondents in areas with limited access to health facilities, divided into experimental and control groups. Data is collected through application usage logs and questionnaires, analyzed using appropriate statistical techniques to evaluate accessibility and user satisfaction. The results show that the LBS application significantly increases the accessibility of health facilities. The experimental group found and accessed health facilities 30% faster than the control group. As many as 85% of experimental group respondents were satisfied with the ease of use and speed of application access. The LBS application is effective in increasing the accessibility of health services by providing real-time information about nearby health facilities. This research has practical implications for app developers, healthcare providers, and policymakers.